Adjustment factors for direct-embedded transmission pole foundations - Kalaga, Sriram (Journal of Structural Engineering, 2024)
Current guidelines for determining direct embedment depths for tangent transmission poles are evaluated. Embedment depths from approaches based on pole stability as well as lateral resistance are compared. Numerical embedment calculations are performed in three different types of soils – moist sand, submerged sand and saturated clay – using two specific computer programs, for moderate ground line reactions. Based on the results, nominal adjustment factors for industry typical embedment depths are proposed for the three soil types. Suggestions for future extensions of the approach are made.